The effect of nursing and rehabilitation measures on quality of life and expression of Bax/Bcl2 genes in patients with stroke: Rehabilitation nursing on stroke patients - Zhang, Beibei; Li, Jing; Chen, Jianyong (Cellular and Molecular Biology, 2022)
Stroke is the leading cause of neurological problems and the third leading cause of death globally, leading to various neurological defects. Due to the importance of applying nursing and rehabilitation measures to reduce complications in these patients, a study was conducted to determine the effect of nursing and rehabilitation measures on the quality of life of patients with stroke. This two-stage experimental study (before and after) was performed on 20 patients with stroke admitted to the internal medicine department. Patients were selected by sampling method, which had inclusion criteria. Data were collected using a questionnaire based on the quality of life in four areas of physical, mental, general health, and social functioning before and after the intervention. Real-Time PCR measured the expression of Bcl2 / Bax genes. Descriptive and inferential statistics analyzed the data. The results showed that the mean quality of life scores in physical function, psychological, social position, and general health after nursing and rehabilitation measures increased significantly (p = .05). Also, the quality of life score after these measures had a significant increase compared to before (p = .05). Also, a significant increase was observed in the expression ratio of the Bcl2 / Bax genes in the study group compared to the control group, which indicates the effect of nursing and rehabilitation measures on cerebral ischemia. The findings showed that the application of nursing and rehabilitation measures positively affects various aspects of patients' quality of life with stroke. These programs should be provided while educating patients and their families to help them achieve greater independence in the future.